Moderating Role of Emotional Labour in Job Characteristics and Organizational Commitment Relations - Oranika, Ndidi G.; Okonkwo, Ejike A.; Aboh, Uche J. (International Journal of Social and Administrative Sciences, 2020)
This cross-sectional study investigated the moderating role of emotional labour in job characteristics and organizational commitment relations among secondary school teachers in Enugu urban area of Enugu State, Nigeria. One hundred and eighty (180) teachers, comprising 62 men and 118 women between the ages of 22 to 61 years were sampled using multi-stage sampling techniques. The 18-item Organizational Commitment Scale, 21-item Job Characteristics Scale and 10-item Emotional Labour Scale were the measures for data collection. Results of moderated regression analysis revealed that the various dimensions of job characteristics and emotional labour did not equally predict organizational commitment. And the two components of emotional labour did not equally moderate. Job characteristics and emotional labour accounted for 9.6% of the variance in affective commitment of the teachers, 10.6 % of variance in continuance commitment and 18.6% in normative commitment. Specifically, feedback from agents’ dimension of job characteristics independently predicted normative commitment while the other dimensions did not predict any dimension of organizational commitment. Surface acting negatively predicted affective commitment while deep acting positively predicted continuance commitment. Deep acting strengthened the relationship between feedback from agents and affective commitment while surface acting weakened the relationship between feedback from agents and continuance commitment. Surface acing strengthened the relationship between feedback from job and continuance commitment. Surface acting also strengthened the relationship between dealing with others and normative commitment. This study has recommended that policy makers in teaching/education should consider job characteristics and emotional labour in order to enhance organizational commitment.